Supporting Teachers of Pre-primary Education to Develop Children’s Thinking (Interdisciplinary Research in Teaching and Learning: New Perspectives and Approaches, 2024)
The aim of the paper is to present innovative teaching approaches to theoretical and practical modules, which were designed to support students of the pre-school education study programme in the field of communication and critical thinking development. Data were collected through content analysis of student seminar papers (N=185) and from student reflective reports (N=185). Data were analysed using open and thematic coding. The results indicated that students who had the opportunity to study in an integrated course with the use of supportive materials achieved better results in all monitored categories than students studying according to the original study plan. This comparison highlights the importance of an integrated approach to the preparation of future teachers, where they gain a holistic view of the studied issue within the framework of large teaching modules.